Performance behaviour of macro-synthetic fibre reinforced concrete subjected to static and dynamic loadings for sleeper applications. (8th February 2021) - Camille, Christophe; Kahagala Hewage, Dayani; Mirza, Olivia; Mashiri, Fidelis; Kirkland, Brendan; Clarke, Todd
Abstract: This paper presents the evaluation of macro-synthetic fibre reinforced concrete (MSFRC) structural performances under both static and dynamic loadings. The innovative composite material is assessed in terms of mechanical properties (i.e. workability, compressive, indirect tensile & flexural strengths) and failure mechanisms as compared to plain concrete. Accordingly, the novelty of this paper is to present the performance of different fibres' characteristics (i.e. aspect ratio) and dosages of long polypropylene-based fibres implemented for sleeper applications. Characteristically, macro-synthetic fibre reinforcement is used towards improving the durability of concrete and reducing the damage caused through thermal cycles. In the tests performed, the fibre reinforced concrete has been proposed to minimise the static and dynamic failure modes while as anticipated improve the post-cracking behaviour.